ODONATA DIVERSITY AT THE MOUNT PERMISAN NATURAL TOURISM PARK SOUTH BANGKA REGENCY, BANGKA BELITUNG - Ani Tias Kusumaningrum; Henri Henri; Herry Marta Saputra (Universitas Medan Area, 2022)
Mount Permisan Natural Tourism Park, South Bangka regency is a conservation area that contains flora and fauna. The diversity of fauna in conservation areas is important to note because fauna can maintain the balance of natural ecosystems. This study aims to analyze the diversity of species and the effect of habitat characteristics on the Odonata population. Odonata sampling was carried out using an insect net randomly at a predetermined point in the left and right directions of the 100 m transect line. Identification was carried out at the Entomology Laboratory, Agricultural Quarantine Center Pangkalpinang, and compared with a comparison sample at the Zoology Laboratory, Biology Department, Universitas Bangka Belitung. Based on the research that has been done, found 14 species of Odonata from the sub-order Anisoptera and 11 species of damselfishes from the sub-order Zygoptera. The species diversity at that location was classified as moderate because H' was 1.56 to 2.05. The evenness value is high with a value of 0.62 to 0.90. The species of wealth (Margalef) is in the range of values from 2.55 to 2.75 which indicates the species richness of dragonflies in the Mount Permisan Natural Tourism Park index is classified as moderate.